Pengaruh Kualitas Pelayanan dan Nilai Nasabah terhadap Kepuasan Nasabah Pada PT. Stanford Teknologi Indonesia di Jakarta Pusat - Bernadus Buulolo (Global Leadership Organizational Research in Management, 2024)
Financial Technology Peer to Peer (P2R) company continues to grow. However, in its implementation there are still shortcomings, especially related to service quality, customer value, and customer satisfaction. This study aims to analyze the effect of service quality and customer value on customer satisfaction of PT. Stanford Teknologi Indonesia. The research method used is quantitative with a research sample of 97 respondents with the Cochran formula, and the analysis used is multiple linear regression. From the results of this study, service quality (X1) has a positive and significant effect on customer satisfaction (Y) obtained t count> t table (5.413> 1.988) and a significance of 0.000 <0.05 which means that service quality (X1) has a positive and significant effect on customer satisfaction (Y). Customer value (X2) has a positive and significant effect on customer satisfaction (Y) from the calculation of t count> t table (2.323> 1.988) and a significance of 0.019 <0.05 which means that customer value (X2) has a positive and significant effect on customer satisfaction (Y). Simultaneously, service quality (X1) and customer value (X2) have a positive and significant effect on customer satisfaction (Y) from F count > F table (7.878 > 2.460) with a significance level of 0.000 < 0.05. The results of the determination coefficient obtained R Square 75.9%. influenced by service quality (X1) and customer value (X2) while the remaining 24.1% is influenced by other variables outside this study.